Ultrathin Solid Polymer Electrolyte Design for High‐Performance Li Metal Batteries: A Perspective of Synthetic Chemistry. Issue 1 (28th November 2022) - Wang, Qian; Wang, Shi; Lu, Tiantian; Guan, Lixiang; Hou, Lifeng; Du, Huayun; Wei, Huan; Liu, Xiaoda; Wei, Yinghui; Zhou, Henghui
Abstract: Li metal batteries (LMBs) have attracted widespread attention in recent years because of their high energy densities. But traditional LMBs using liquid electrolyte have potential safety hazards, such as: leakage and flammability. Replacing liquid electrolyte with solid polymer electrolyte (SPE) can not only significantly improve the safety, but also improve the energy density of LMBs. However, till now, there is only limited success in improving the various physical and chemical properties of SPE, especially in thickness, posing great obstacles to further promoting its fundamental and applied studies. In this review, the authors mainly focus on evaluating the merits of ultrathin SPE and summarizing its existing challenges as well as fundamental requirements for designing and manufacturing advanced ultrathin SPE in the future. Meanwhile, the authors outline existing cases related to this field as much as possible and summarize them from the perspective of synthetic chemistry, hoping to provide a comprehensive understanding and serve as a strategic guidance for designing and fabricating high‐performance ultrathin SPE. Challenges and opportunities regarding this burgeoning field are also critically evaluated at the end of this review. Abstract : This study mainly focuses on the trend of applying established synthetic chemistries in manipulating the thickness of SPE to bridge its incorporations with practical electrochemical devices with high‐energy‐density LMBs. The advantages and existing challenges of ultrathin SPE are discussed, while the progress of ultrathin SPE based on synthetic chemistry are summarized and several typical fabrication methods are looked back upon.